The Architecture of Encounter: Intercultural Communication, Collaboration, and Community Immersion as Pedagogical Space - Yu, Yonghyun; Wijayaputri, Caecilia Srikanti; Gunawan, Yenny; Pujianto, Franseno; Partana, Yonav (UI Scholars Hub, 2025)
Being community responsive in such a multicultural context requires an intercultural approach to bridge the mutual understanding and collaboration. There is a surge to introduce intercultural learning to students within their role as a global community. This study analyzes the 2023 International Architecture Workshop (IAW) taking place in Bali, a collaboration among the University of Ulsan, Universitas Gunadarma, and Parahyangan Catholic University, through the lens of intercultural learning. Due to an increasing demand for intercultural competence, transnational collaboration, and community-responsive design literacy, this workshop provides important capacities in architectural education. This workshop shows how a situated pedagogy can reconfigure students’ design processes, highlighting cross-cultural and community-embedded encounters. Drawing on participant observation, field documentation, informal interviews, and design analysis, the study demonstrates how communication across linguistic and cultural differences operated as a multi-channel problem-solving activity. The immersive experiences of participants in the village have foregrounded local knowledge as relational, performative, and ecologically situated, disrupting abstract and studio-bound design habits. The workshop further revealed how heterogeneous institutional cultures crystallized into distributed expertise, producing hybrid and collective strategies through iterative negotiation rather than individual authorship. The findings of this study show that multi-channel communication practices enabled intercultural comprehension, distributed expertise generated hybrid forms of collective authorship, and community immersion sharpened sensitivity to cultural, ecological, and social conditions. These findings affirm how the pedagogical value can be situated, encouraging community-engaged learning. The study positions the IAW as a transferable model for intercultural and community-responsive architectural education within the ASEAN region.